2020
DOI: 10.1039/d0ra00305k
|View full text |Cite
|
Sign up to set email alerts
|

Boosting CO2 adsorption and selectivity in metal–organic frameworks of MIL-96(Al) via second metal Ca coordination

Abstract: MIL-96(Al)–Ca1 shows the highest CO2 adsorption capacity; while MIL-96(Al)–Ca4 displays a distinguished morphology with the highest selectivity of CO2/N2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 73 publications
2
22
0
Order By: Relevance
“…erefore, removing of Ca from UiO-66-Ca increased the active sites and consequently enhanced the adsorption capacity of MB [81].…”
Section: Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…erefore, removing of Ca from UiO-66-Ca increased the active sites and consequently enhanced the adsorption capacity of MB [81].…”
Section: Characterisationmentioning
confidence: 99%
“…Also, the adsorption capacity in UiO-66-Ca 10% and UiO-66-30%Ca was higher than that of UiO-66. It was reported that vacant metal sites in bimetallic MOFs are enhanced a er removing the second metal by the solvent exchange activation [81].…”
Section: Characterisationmentioning
confidence: 99%
“…Gas adsorption and separation are the main applications of MOFs due to their large surface areas. Abid and co‐workers [61] investigated into CO 2 capture of MIL‐96(Al) and it exhibited excellent CO 2 adsorption capacity and chemical stability. This research was improved by coordinating metal Ca as the second metal of the MOF by using the hydrothermal method.…”
Section: Effect Of Various Metals and Ligands On Mof Propertiesmentioning
confidence: 99%
“…Recently, metal-organic frameworks (MOFs) have been regarded as promising materials for gas storage and separation [1][2][3][4], catalysis [5][6][7], drug delivery [8,9], sensing [10] and other application areas [11] due to their high permanent porosity, ultrahigh surface area and diverse chemical functionalities. Zeolitic-imidazolate frameworks (ZIFs) are a subclass of MOFs, in which metal ions (e.g., Co, Zn, Cu) are tetrahedrally bonded to the N atoms of imidazolate linkers [12][13][14].…”
Section: Introductionmentioning
confidence: 99%